Boris Vipper and the Soviet Art-Critical Tradition - Rykov, Anatolii V. (Actual Problems of Theory and History of Art, 2022)
The paper considers problems of interpretation of the scientific heritage of Boris R. Vipper (1888–1967) and the tradition of the Soviet art criticism of the 1950s –1960s. Various aspects of the art critic’s work (scientific, cultural, and ideological) are investigated. The sources of B. Vipper’s art criticism and cultural views are identified and analyzed. At the same time, special attention is paid to the impact of German classical art criticism on the Vipper’s works and to elements of populist art criticism in his writings. The analysis of the works of Tintoretto, Giovanni Pisano, and Donatello in the works of B. Vipper is evaluated in connection with the reconstruction of the “modernist rhetorical complex” in his works. The differences in the methodological strategies of creativity of B. Vipper and A. Gabrichevsky are revealed. B. Vipper’s methodology is studied in the context of expressionistic aesthetics and its refractions in art history and popular cultural studies. The author comes to the conclusion about the relative unity of B. Vipper’s methodological techniques of various periods of his work and the scientific parameters of the ’canon’ of the Soviet art history tradition of the 1950s –1960s. The rhetorical and cultural discourses involved in the texts of B. Vipper, on the contrary, come into conflict with the ideological parameters of Soviet art criticism. The ’modernist rhetorical discourse’ in the works of B. Vipper characterizes to a greater extent the cultural rather than scientific aspects of the scientist’s work.